FEMININITAS DALAM DESAIN KONTEN INSTAGRAM @DOA.INDONESIA: ANALISIS SEMIOTIKA IKLAN JUDITH WILLIAMSON - Neng Eva (UNIVERSITAS NUSA PUTRA, 2022)
This research tries to explore ideology and how advertising works to make the target audience aware of the Femininity side of Instagram Feed Design @Doa.indonesia. Various theoretical concepts in Judith Williamson's (1979) ad semiotics are used as a scalpel to find out the meaning contained in Instagram Feed Design @Doa.indonesia. signifier, signified, generator, currency. Looking at the results of the analysis in the five Instagram Feed Designs @Doa.indonesia, which is dominated by the signifier scalpel and ends in the currency scalpel. in which there are signs that refer to femininity and the design has a different target exchange value. This @Doa.indonesia product shows the diversity of femininity to return to upholding the true value of femininity in women.